Multiple Splenic Artery Aneurysms: A Case Report and Review of the Literature - Chen, Wen Chun; Wang, Tie hao; Yuan, Ding; Zhao, Ji Chun (Frontiers in Surgery, 2022)
Abstract Background: Multiple splenic artery aneurysms (MSAAs) are rare and there are few reports about their treatment. We herein present a rare case of MSAAs treated with splenectomy combined with endovascular embolization. Methods: A 51-year-old female patient was incidentally diagnosed with MSAAs. Splenectomy combined with endovascular embolization was the chosen treatment. outcomes: The patient recovered uneventfully and was discharged from the hospital five days after splenectomy. The patient has been doing well during the 27-months of follow-up. Conclusion: Combined with the experience of the previous literature, we think splenectomy combined with endovascular embolization is a safe, reliable and minimally invasive treatment for some selected multiple SAAs, depending on several patient parameters, such as the age, sex, aneurysm dimension, aneurysm location, complications, and severity of the clinical findings.